INTEGRATED TEAM COLLABORATION FOR MANINJAU LAKE RESCUE IN OVERCOMING THE SULFU TUBO PHENOMENON: KOLABORASI TIM TERPADU PENYELAMATAN DANAU MANINJAU DALAM MENGATASI FENOMENA TUBO BELERANG - Aulia, Nanda; Rizki Syafril (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Law Number 32 of 2009 on Environmental Protection and Management emphasizes the importance of environmental conservation to prevent pollution and degradation. Within the context of regional autonomy, local governments have the authority to manage natural resources and involve the community in environmental protection. Lake Maninjau, one of the natural assets in Agam Regency, West Sumatra, faces serious pollution issues due to the tubo belerang phenomenon and the uncontrolled growth of floating net cages (KJA). This phenomenon has led to mass fish deaths and adversely affected the ecosystem and the livelihoods of those who depend on the lake. The Agam Regency Government has formed an Integrated Team for the Rescue of Lake Maninjau through Agam Regent Decree Number 263 of 2021. However, the team’s tasks have encountered various challenges, such as a lack of coordination and limited resources. This study aims to analyze the collaboration of the Integrated Team in addressing the tubo belerang phenomenon in Lake Maninjau and evaluate the effectiveness of the actions taken. It is hoped that the results of this research will provide recommendations for improving the sustainable management and conservation of Lake Maninjau.